Exploring Communication and Cultural Adaptation Practices Among Indonesian Diaspora Students at McGill University, Canada - Muhammad Rifa'at Adiakarti Farid; Latutik Mukhlisin; Fajar Junaedi; Eka Anisa Sari (Profetik: Jurnal Komunikasi, 2025)
This study discusses the communication and cultural adaptation of Indonesian diaspora students who are studying abroad. The background of this research is rooted in the need to understand how students adjust to their surrounding environment and how they experience cultural adaptation while pursuing education overseas, where the culture and language differ from those of their hometowns. It is undeniable that Indonesian students face various challenges when studying abroad, such as adapting to a new environment, unfamiliar habits, and different patterns of interaction with groups or individuals. These challenges are influenced by several factors, including time, climate, academic environment, food, ethics, language, location, and cultural values, all of which have distinct characteristics. Barriers to communication adaptation can be observed in the ongoing communication process. The influencing factors include the communicators’ linguistic ability, the clarity of messages, the communication media used, the characteristics of the communicants, and the level of reciprocity within the communication interaction. This study employs a qualitative descriptive method, with Indonesian doctoral diaspora students at McGill University, Canada, serving as the research subjects. The results show that respondents needed time to adjust to their environment before they were eventually able to adapt well. The study concludes that adaptation, particularly the ability to understand the local culture and language plays a crucial role in enabling students to adjust successfully.